2021
DOI: 10.26858/ijole.v5i1.16002
|View full text |Cite
|
Sign up to set email alerts
|

Examining Students’ Challenges in Oracy in Academic Context Classes

Abstract: This study identifies challenges perceived by Indonesian students of English as a Foreign Language in Oracy in Academic Context classes as well as possible causes of the problems. This subject was a new addition to the 2018 curriculum of the English Department of Teacher Training and Education Faculty at XXX University in Indonesia. The findings show the main problems students faced related to speaking issues, for example, lack of self-confidence, fear of making mistakes, ineffective class schedule, annoying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This theme is important because language education aims to promote awareness of critical thinking, to practice critical thinking, and to evaluate and assess critical thinking both from learners and educators. Examples of cognitive and critical thinking are in language education such as Lailiyah & Wediyantoro, (2021); Wahyuni, Maulina, & Mulia, (2021); Harahap & Astrid, (2021); Riwayatiningsih et al (2021); Wulandari et al, (2021).…”
Section: Discussionmentioning
confidence: 99%
“…This theme is important because language education aims to promote awareness of critical thinking, to practice critical thinking, and to evaluate and assess critical thinking both from learners and educators. Examples of cognitive and critical thinking are in language education such as Lailiyah & Wediyantoro, (2021); Wahyuni, Maulina, & Mulia, (2021); Harahap & Astrid, (2021); Riwayatiningsih et al (2021); Wulandari et al, (2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is actually admitted that motivation gives them momentum to TEFL classrooms (Ibid, 2021: 2). Wulandari et al (2021) found that while speaking in English, a component of communication in English, EFL students had more challenges, such as lack of selfconfidence, fear of committing mistakes, ineffective class schedule, irrelaxing audience behaviour, lack of vocabulary, grammatical imprecision, improper pronunciation, hard and unintruiging topics, immediate corrective feedback, besides problems coordinating group work. The study also added that, as listeners, the students had difficulties caused by their lack of adequate background knowledge, unfamiliar vocabulary, anxiety, speakers" inappropriate pronunciation, too fast or too long presentations, various accents, sound clarity.…”
Section: Challenges During Communicationmentioning
confidence: 99%
“…The challenges in oracy assessment are related to internal factors, such as lack of selfconfidence, fear of making mistakes, lack of vocabulary, lack of grammatical mastery, poor pronunciation, and difficulty in coordinating in group work, which is mostly influenced by psychological and competence aspects, and the external factors, such as an ill-timed class schedule, annoying audiences, broad and uninteresting topics of speech, and direct corrective feedback (Wulandari et al, 2021). These facts reveal the internal and external factors making oracy difficult within the vocational context: this may relate to the difficulty in expression personal and professional idea, collaboration with the team and colleagues, individual psychological types and competence level, relationship with the authority and accepting the criticism.…”
Section: Framework For Oracy Assessmentmentioning
confidence: 99%